PERAMALAN PUNCAK PRODUKSI DAN UMUR CADANGAN BATUBARA DI INDONESIA - Arif Setiawan; Mayang Kinanti Puteri; Yulianus Rombe Pasalli (Jurnal Teknologi Mineral dan Batubara, 2023)
Indonesia is a country that has quite large resources and reserves (3.25%) of the world's coal reserves. Indonesia's coal production in 2022 will reach 687 million tonnes to meet domestic and foreign (export) demand. Indonesia's coal production from year to year has an increasing trend. The existence of this upward trend can result in a decrease in the number of existing coal reserves. This study aims to predict the peak of coal production by estimating the age of the existing reserves. The data used is annual data from 1996 to 2021. The coal reserves used as a basis for consideration are 36,278.85 million tons. The methods used to forecast coal peak production and reserve age are the Hubbert, logistics, and Gomperzt models. The results obtained explain that the peak of coal production occurred in 2018 amounting to 0.539 billion tons with a coal reserve until 2081. For the logistic and Gomperzt models, the peak of coal production occurred in 2033 amounting to 1.345 billion tons and 0.7604 billion tons. Meanwhile, the reserve ages of the two models until 2080 and 2120.